2009
DOI: 10.1371/annotation/8d99ccc5-cc76-44f4-b468-d63e42e0b9e1
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Cellular Communication through Light

Abstract: Information transfer is a fundamental of life. A few studies have reported that cells use photons (from an endogenous source) as information carriers. This study finds that cells can have an influence on other cells even when separated with a glass barrier, thereby disabling molecule diffusion through the cell-containing medium. As there is still very little known about the potential of photons for intercellular communication this study is designed to test for non-molecule-based triggering of two fundamental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The DEA approach using the method of stripes illustrated in this paper will contribute to progress in this field of research, which is not limited to applications in biological and physiological processes. The discussion on the origin of cognition moves from the elementary biological process, for instance cell to cell communication [59][60][61], generating the conjecture that this is based on quantum mechanical coherence, one form of non-commutative probability theory, a theoretical perspective that we believe to be related to SFBM processes on the basis of the fact that the dynamical approach to FBM [4] was derived by the quantum mechanical theory of quantum dissipative processes of Weiss [62]. We think that at this elementary biological level crucial events, namely form of compressible randomness, are generated by SOTC.…”
Section: Discussionmentioning
confidence: 99%
“…The DEA approach using the method of stripes illustrated in this paper will contribute to progress in this field of research, which is not limited to applications in biological and physiological processes. The discussion on the origin of cognition moves from the elementary biological process, for instance cell to cell communication [59][60][61], generating the conjecture that this is based on quantum mechanical coherence, one form of non-commutative probability theory, a theoretical perspective that we believe to be related to SFBM processes on the basis of the fact that the dynamical approach to FBM [4] was derived by the quantum mechanical theory of quantum dissipative processes of Weiss [62]. We think that at this elementary biological level crucial events, namely form of compressible randomness, are generated by SOTC.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the influence of ambient light on the behaviours of microorganisms is now well established, communication by light emitted by luciferases of bioluminescent unicellular organisms has not been previously addressed. Previous studies have brought experimental evidence that non-bioluminescent prokaryotic and eukaryotic unicellular organisms such E. coli and Paramecia communicate between themselves through the emission and reception of weak photons [ 264 , 295 , 296 , 297 ]. It is therefore likely that organisms that have evolved specific bioluminescent systems to emit more intense light and modulate light intensity communicate with each other or with other species through light.…”
Section: Hypothesis: Bioluminescence Signalling In the Unicellular Worldmentioning
confidence: 99%
“…Since the 1930s photon emissions have been recorded from all living systems (Gurwitch, 1926). The rejuvenation of these measurements, primarily stimulated by Popp (1979), has indicated that the photon emissions are not simply metabolic artifacts but are intimately involved with inter-cell and intra-cell communications (Trushin, 2009;Fels, 2009). Popp (1979) has argued that because all (or simply most) of the energy that has contributed to the evolution of biological systems on this planet originates from the sun, "virtual photons" that reflect this history are represented within the matter of the cell.…”
Section: "Spiritual" Energy As "Quantum" Level Energymentioning
confidence: 99%